11th INTERNATIONAL WEEK PROMOTING UNIQUE AND DIVERSE INTERNATIONAL CULTURES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 22 November 2016 – The 11th International Week, to be held at Universiti Sains Malaysia (USM) this year, will be promoting diverse and unique cultures from different countries to the USM community.